Long-term isolation and archaic introgression shape functional genetic variation in Near Oceania - Reilly, Patrick F.; Rong, Stephen; Tejada-Martinez, Daniela; Miller, Samantha L.; Tjahjadi, Audrey; Liu, Chang; Akers, Jared; Pomer, Alysa; Prentice, Margaret E.; Merriwether, D. Andrew; Friedlaender, Françoise R.; Koki, George; et al. (Science, 2026)
INTRODUCTION Because of their different settlement histories, the Pacific Islands have been divided into Near and Remote Oceania. Near Oceania—the region consisting of New Guinea, the Bismarck Archipelago, and the main Solomon Islands—was settled ~42,000 years ago and thereafter remained largely isolated at the edge of human settlement. Not until ~5000 years ago, with the advent of new migration pressures from Asia, were the rest of the Pacific Islands inhabited—Remote Oceania, encompassing Vanuatu, New Caledonia, Fiji, Polynesia, and Micronesia. Near Oceanic populations harbor substantial cultural, phenotypic, and genetic diversity, including the largest amounts of archaic introgression inherited from Neanderthals and Denisovans. However, they have been substantially underrepresented in whole-genome sequencing and functional genomic consortia to date. RATIONALE We sequenced 177 high-coverage genomes from 12 diverse Near Oceanic populations and analyzed them alongside 1284 genomes from worldwide populations. We investigated the demographic history of groups descended from early settlers of the Pacific and the extent and distribution of Neanderthal and Denisovan introgression in Near Oceanic genomes, including adaptive archaic variation, and performed a massively parallel reporter assay to identify the functional consequences of adaptive archaic introgressed variants. RESULTS Near Oceanians in our study fall along a gradient of genetic similarity from Papuan-speaking groups of New Guinea and the Baining of New Britain to the Polynesian outlier groups of the Solomon Islands, although we also observed signals of long-term isolation in Papuan-speaking groups. Furthermore, both the Baining and Polynesian outlier groups showed evidence of major population bottlenecks, emphasizing complex population structure and demographic history in this region. We reconstructed archaic introgressed sequence covering 70.7% of the callable archaic genome (1.897 billion base pairs) including 505 million base pairs (Mbp) of previously unidentified archaic sequence and three times more Denisovan sequence than previous studies (831.9 Mbp). We uncovered evidence for introgression from three Denisovan-like groups into the ancestors of Near Oceanians, revealing a new twist on our interactions with archaic hominins. We refined maps of archaic “deserts” and identified a strong novel signal of adaptive Denisovan introgression at TRPS1, a skeletal development gene previously found under selection in central African rainforest hunter-gatherers and highland Ecuadorians. Using a massively parallel reporter assay, we discovered 3127 high-frequency introgressed expression-modulating variants targeting 1422 genes and found an enrichment of high-frequency introgressed variants with protein-coding, splicing, and regulatory impacts on immune pathways. These include adaptive archaic variants affecting genes in the interferon-γ pathway, including JAK1, GBP2, and the COVID-19–associated OAS1 locus, where we functionally characterized a Denisovan haplotype unique to Oceanic populations. Although some of these adaptive introgression signals, such as TNFAIP3 and HLA-DRA, may be related to malaria susceptibility, few are widely shared across Near Oceania, suggesting multiple independent instances of local adaptation. Many of these immune-related genes are also pleiotropic, including TRPS1 and TANK. CONCLUSION We characterized the evolutionary, phenotypic, and functional consequences of archaic introgressed variants in Near Oceanians and identified putatively causal archaic variants contributing to parallel local adaptation of both the immune system and skeletal development.